1989
DOI: 10.1007/bf00190204
|View full text |Cite
|
Sign up to set email alerts
|

Strain differences in amiloride inhibition of NaCl responses in mice, Mus musculus

Abstract: The effects of lingual treatment with amiloride, an inhibitor of salt taste responses in several mammalian species, on NaCl responses of the chorda tympani nerve were compared between four inbred strains of mouse (BALB/cCrSlc, DBA/2CrSlc, C57BL/6CrSlc and C3H/HeSlc). In C57BL and C3H mice amiloride significantly suppressed responses of the chorda tympani nerve to NaCl at a concentration 0.1 M or more whereas in BALB and DBA mice the drug did not significantly affect the responses to NaCl at any concentration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
61
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 30 publications
8
61
0
Order By: Relevance
“…These results provide new characteristics of salt acceptance in the mouse and together with the previous data (2)(3)(4)19,23,32), they show that the range of responses to sodium, potassium and calcium salts is similar in mouse and rat strains (1,8,21,28,29).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results provide new characteristics of salt acceptance in the mouse and together with the previous data (2)(3)(4)19,23,32), they show that the range of responses to sodium, potassium and calcium salts is similar in mouse and rat strains (1,8,21,28,29).…”
Section: Discussionsupporting
confidence: 81%
“…The BPN and BPL mouse strains had strong preferences for 37.5-150 mM NaCl compared with the BPH strain tested here and mouse strains tested in other studies, which either only moderately preferred these NaCl concentrations, or did not prefer them at all (2)(3)(4)19,23). The BPH, BPN and BPL mice originate from a population derived from an eight-way cross of eight inbred mouse strains (25).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The diuretic agent amiloride, a sodium channel blocker, selectively suppresses taste responses to NaCl, but not to sweet, sour, and bitter substances in many mammals (Schiffman et al, 1983, Heck et al, 1984, Jakinovich 1985, Simon et al, 1986, Herness 1987, Ninomiya et al, 1989, Hellekant and Ninomiya, 1991. Subsequent studies using amiloride in rodents suggested that two distinct components underlie cellular sensitivity to NaCl: one that is amiloride-sensitive and another that is amilorideinsensitive.…”
Section: Neural and Molecular Mechanisms Of Salt Taste Perceptionmentioning
confidence: 99%
“…Therefore, ENaC was predicted to be a potential amiloride-sensitive salt taste receptor based on the results of multiple studies (Schiffman et al, 1983, Heck et al, 1984, Jakinovich 1985, Simon et al, 1986, Herness 1987, Ninomiya et al, 1989, Hellekant and Ninomiya, 1991. It was demonstrated several years ago that the ENaC α-subunit (αENaC) plays an essential role as a receptor for amiloride-sensitive sodium taste in mice, since taste-cell-specific αENaC knockout (KO) mice exhibited a complete loss of amiloride-sensitive sodium taste response without any effect on responses to other salts or sweet, umami, bitter and sour substances (Chandrashekar et al, 2010).…”
Section: Neural and Molecular Mechanisms Of Salt Taste Perceptionmentioning
confidence: 99%